Atrial natriuretic peptide in physiological doses does not inhibit the ACTH or cortisol response to corticotrophin-releasing hormone-41 in normal human subjects. - Ur, E; Faria, M; Tsagarakis, S; Anderson, J; Besser, G; Grossman, A (1991)
Whilst it has been postulated that atrial natriuretic peptide (ANP) may modulate pituitary hormone release, several investigations in non-human species have reported conflicting results when looking for an effect on the hypothalamo-pituitary-adrenal axis. However, in a recent study significant inhibition of corticotrophin-releasing hormone (CRH)-stimulated ACTH in cultured rat anterior pituitary cells occurred only with the complete peptide alpha-ANP(1-28). We have therefore investigated whether this form of ANP can inhibit CRH-stimulated ACTH and cortisol release in human subjects. Six healthy male volunteers received human alpha-ANP or placebo, and human CRH or placebo, on four separate occasions. ANP was infused at a rate of 0.01 micrograms/kg per min in order to achieve levels in the high physiological range. CRH was given as a bolus dose of 100 micrograms 30 min into the ANP infusion. Cortisol and ANP were measured by radioimmunoassay, the latter after extraction. ACTH was measured by immunoradiometric assay. The data were analysed by Student's paired t-test on basal, peak and incremental levels. Basal levels of ANP were within the normal range (2-5 pmol/l). With ANP infusion, mean +/- S.E.M. peak ANP levels were 29.6 +/- 3.1 pmol/l. There were no significant differences in mean basal cortisol and ACTH levels on each of the 4 study days. Mean peak cortisol and ACTH levels after CRH and ANP did not significantly differ from those achieved with CRH and placebo ANP. We thus conclude that at high physiological doses, circulating ANP does not inhibit CRH-stimulated ACTH or cortisol release.